2012
DOI: 10.1075/rcl.10.1.04ser
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring verbs in Spanish

Abstract: The objective of the present study focuses on exploring two proposals about the acquisition of the grammatical category of verb. On the one hand, the study aims at analyzing whether the acquisition of a given mass of verbal lexical items occurs before the emergence of productive verbal morphology. On the other hand, the study also explores the possibility that the acquisition of negative structures emerges before productive verbal morphology as well. The study presents longitudinal data based on the linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Possibly, childrenas opposed to adult L2 learnersare positively activated by this factor. Serrat et al (2012) have examined the lexical spurt issue in relation to the maturation of some relevant syntactic indicators. They observed that Spanish and Catalan children learn the productive use of negation before the burst of verb morphology productivity.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Possibly, childrenas opposed to adult L2 learnersare positively activated by this factor. Serrat et al (2012) have examined the lexical spurt issue in relation to the maturation of some relevant syntactic indicators. They observed that Spanish and Catalan children learn the productive use of negation before the burst of verb morphology productivity.…”
Section: Summary Of the Resultsmentioning
confidence: 99%